Pelatihan “PLANS” untuk Meningkatkan Efikasi Diri dalam Pengambilan Keputusan Karir - Difa Ardiyanti; Asmadi Alsa (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
Self-efficacy has an important role in career decision-making. The collected data showed that there were some students (grade 11 and grade 12) had confused to decide their career choice. The data proved that career guidance is necessary for high school students. If students get assistance earlier, students will be more confident to make career decisions in their future. Therefore, the \"PLANS\" training was given to grade 11’s students. The goal was to increased student’s career decision-making self-efficacy. This quasi experiment conducted using the untreated control group design with dependent pretest and post test samples using double pretest. Data were collected using Career Decision-Making Self-Efficacy Scale. The subjects were 34 students of grade 11 who had medium career decision-making selfefficacy (16 students of experiment group and 18 students of control group). The result showed that career decision-making self-efficacy of experiment group is higher than control group after “PLANS” training. The “PLANS” training contribute to 73% of career decision-making self-efficacy improvement.